UPAYA PENYELESAIAN PERMASALAHAN ANTARA PENCIPTA PEMEGANG HAK CIPTA DAN PIHAK KE TIGA YANG MENGGANDAKAN BUKU BUDAYA MELAYU RIAU TANPA IZIN DALAM PRESFEKTIF UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Yesi Fitri Indriani; Zulfikar Jayakusuma; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Reproduction and distribution of books without the permission of the copyright holder is a violation of law 28 of 2014. Copyright consists of economic rights and moral rights. Economic rights are rights to obtain economic benefits from creations and related rights products. Moral rights are rights inherent in the creator or actor that cannot be removed or deleted without any reason, even though the Copyright or Related Rights have been transferred. The purpose of writing this thesis: first, to find out how the legal position of the parties in a copyright license without a written agreement according to the copyright law Second, to find out what are the efforts to resolve problems between the creator of the copyright holder and the third party who reproduces the Riau Malay Culture Book without permission in the Prefective Law Number 28 of 2014 concerning Copyright The research that the author conducted is included in the type of normative juridical research which means finding the truth of the coherence of how the law operates in society. If viewed from the nature of this research is descriptive.          The author's suggestion in this study is to suggest that an agreement be made between the copyright holder and the publisher either orally or in writing so as to provide legal force that binds the copyright agreement. As the copyright holder has exclusive rights to the results of his creation (books) if not done the agreement, the legal consequences of granting a copyright license without a written agreement, the agreement is null and void, Suggest that the case be resolved in a commercial court because copyright prohibition is a prohibition that is included in the violation of intellectual property rights in the form of a book Keywords: Copyright, -Agreement